The Pastoral Origin of Semiotically Functional Tonal Organization of Music - Nikolsky, Aleksey (Frontiers in Psychology, 2020)
This paper presents a new line of inquiry into when and how music as a semiotic system was born. Eleven principal expressive aspects of music each contains specific structural patterns whose configuration signifies a certain affective state. This distinguishes the tonal organization of music from the phonetic and prosodic organization of natural languages and animal communication. The question of music’s origin can therefore be answered by establishing the point in human history at which all eleven expressive aspects might have been abstracted from the instinct-driven primate calls and used to express human psycho-emotional states. Etic analysis of acoustic parameters is the prime means of cross-examination of the typical patterns of expression of the basic emotions in human music versus animal vocal communication. A new method of such analysis is proposed here. Formation of such expressive aspects as meter, tempo, melodic intervals, and articulation can be explained by the influence of bipedal locomotion, breathing cycle, and heartbeat, long before Homo sapiens. However, two aspects, rhythm and melodic contour, most crucial for music as we know it, lack proxies in the Paleolithic lifestyle. The available ethnographic and developmental data leads one to believe that rhythmic and directional patterns of melody became involved in conveying emotion-related information in the process of frequent switching from one call-type to another within the limited repertory of calls. Such calls are usually adopted for the ongoing caretaking of human youngsters and domestic animals. The efficacy of rhythm and pitch contour in affective communication must have been spontaneously discovered in new important cultural activities. The most likely scenario for music to have become fully semiotically functional and to have spread wide enough to avoid extinctions is the formation of cross-specific communication between humans and domesticated animals during the Neolithic demographic explosion and the subsequent cultural revolution. Changes in distance during such communication must have promoted the integration between different expressive aspects and generated the basic musical grammar. The model of such communication can be found in the surviving tradition of Scandinavian pastoral music - kulning. This article discusses the most likely ways in which such music evolved.